Socialisation Experience of New Principals in National Secondary Schools in Penang, Malaysia - Ismail, Norashimah (2008)
This qualitative case study is intended to examine the early socialisation experience of New Principals in national secondary schools in Penang. Socialisation means the familiarisation of new appointees to the demands and challenges of their role, including the structure, culture and work climate where they are appointed. The socialisation is expected to enable new appointees to form an understanding towards their role and vision in the position. In this study the Parkay and Hall (1992) and Tuttle (2002) socialisation model is modified for study context. The subjects were chosen using the purposive sampling method. Eight new principal participants were interviewed, each within the first three years of their appointment. Data were collected using the semi-structured interview method. Data triangulations were compiled by interviewing several teachers at the new principal’s school, and also by examining relevant documents. The findings of the study exhibited the maturity of new principals in carrying out administrative, professional and instructional roles, although all experienced initial cultural shock in their new roles. The appointment or promotion of new principals based on seniority and experience obviously has its benefits, but many new principals were still uncertain on how to respond to the seemingly unsupervised delegation of responsibilities they received from the State Education Department. While a few new principals welcomed the Management by Exception principle practiced by the departments, there were others who hail for more visible support from the department to schools. This study has made a number of suggestions on how the new principals could be assisted.